PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS BLOG UNTUK MENINGKATKAN MOTIVASI BELAJAR X SMAN 1 TANJUNG BUMI - Aini, Kurrotul; Mariatun, Ika Lis; Sholeh, Yusrianto (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
The application of technology in learning as a learning medium will make it easier for students to learn according to their characteristics and can help teachers when overcoming difficulties in conveying learning material. This study aims to determine the procedure for blog-based learning media, and whether or not the learning media is appropriate, as well as to analyze the development or increase in student motivation after the introduction of class X blog-based learning media at SMAN 1 Tanjung Bumi. This study uses research and development methods using the ADDIE model. Using data sources from teachers and students at SMAN 1 Tanjung Bumi, with research data on the development of learning media. Data collection using a questionnaire. Data analysis techniques are qualitative and quantitative data analysis, qualitative data analysis of media is carried out according to the scores of material experts, media experts, economic learning practitioners, and student response questionnaires. The results of research on the development of blog-based learning media in class X OJK lessons with the satisfaction of using blog-based learning media are very suitable for use in learning; student responses experienced an increase in motivation to take part in learning